The Future of Leadership - An Explorative Study into Tomorrow's Leadership Challenges - Eberhardt, Daniela; Majkovic, Anna-Lena (SpringerBriefs in Psychology,, 2016)
This book examines the challenges and social, economic and corporate trends that future leaders will need to deal with, as well as the technical, social and communication skills they will require in order to succeed. This assessment of future leadership overviews the need for a solid base of technical and social skills such as advanced communication and intercultural awareness, all while increasingly need to balance individual and organizational needs. The book begins by discussing the conclusion that future challenges require leaders to operate in increasingly complex and rapidly changing environments while providing a clear strategic vision. This is based upon explorative interviews conducted with 20 academic and practitioner leadership experts, senior consultants, and senior and top managers, many of whom work in innovative organizations in San Francisco and Silicon Valley. Shared are the results prompted by five postulated future economic and social megatrends, the interviewed experts each provided unique insights and views on future work environments and leadership issues. .